1994
DOI: 10.1088/0954-3899/20/1/005
|View full text |Cite
|
Sign up to set email alerts
|

Coulomb dissociation studies as a tool of nuclear astrophysics

Abstract: The Coulomb field of heavy nuclei provides an intense source of quasi-real photons acting on passing nuclear particles. This fact has many applications in studies of problems of nuclear structure and particle physics. In 1984 Coulomb dissociation of fast projectiles was proposed as a novel method to investigate radiative capture processes (time-reversed to photodisintegration). This was a new access to a specific class of radiative capture reactions at low energies, relevant for nuclear astrophysics, and it ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
155
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(159 citation statements)
references
References 81 publications
4
155
0
Order By: Relevance
“…[3], because the fluorine abundances observed in giants can constrain AGB star models [2]. In this context it has been shown that a key isotope for 19 F production in AGB stars is 15 N and a crucial role is played by the 15 N(p, α) 12 C reaction, removing both proton and 15 N nuclei from 19 F production chain in the AGB intershell environment. The available reaction rates have at least an 8% uncertainty in the fluorine surface abundance [2], due to a factor 2 difference between NACRE [4] and CF88 [5] reaction rates usually employed in calculations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3], because the fluorine abundances observed in giants can constrain AGB star models [2]. In this context it has been shown that a key isotope for 19 F production in AGB stars is 15 N and a crucial role is played by the 15 N(p, α) 12 C reaction, removing both proton and 15 N nuclei from 19 F production chain in the AGB intershell environment. The available reaction rates have at least an 8% uncertainty in the fluorine surface abundance [2], due to a factor 2 difference between NACRE [4] and CF88 [5] reaction rates usually employed in calculations.…”
Section: Introductionmentioning
confidence: 99%
“…For charged-particle-induced reactions, such as 15 N(p, α) 12 C, the Coulomb barrier, E C.B. , (about 2 MeV in the present case), is much higher than the energies of interest ( 100 keV), thus implying that the reaction takes place via a tunneling effect with an exponential decrease of the cross section, σ (E) ∼ exp(−2πη) (where η is the Sommerfeld parameter).…”
Section: Introductionmentioning
confidence: 99%
“…The double differential cross-section for the Coulomb excitation of a projectile from its ground state to the continuum, with a definite multipolarity of order πλ is given by [5,6,7] …”
Section: Riken Data E Beam ∼ 50 Mev/nucleonmentioning
confidence: 99%
“…Refs. [5,6]) the measured cross-sections of this reaction to those of the radiative capture reaction b + x → a + γ. Thus, the astrophysical S-factors of the radiative capture processes can be determined from the study of break-up reactions under these conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation